Managing quality risk in supply chain to drive firm's performance: the roles of control mechanisms - Zhang, M.; Ying, Kei Tse; Tan, Kim Hua (Elsevier, 2018)
Product harm scandal can be viewed as a company’s nightmare. In many cases, the source of defective or unsafe components may not be the manufacturing firm itself; rather, there may be problems inherent in the supply network. This research aims to investigate the effects of two focused risk management practices, namely supplier development and proactive product recall, on firms’ performance. To scrutinise the impact of two types of control mechanisms, we investigate social control and formal control as antecedents of risk management practices, and explore their moderating roles on the relationship between risk management practices and firm performance. Based on the survey-based data obtained from 209 Chinese manufacturers, structural equation modelling and hierarchical regression are used to test the proposed hypotheses. The results show that both supplier development and proactive product recall significantly contribute to financial performance and quality performance. Furthermore, both formal control and social control are the significant antecedents of the two risk management practices. Most importantly, we examine the moderating roles of the control mechanisms on the relationship between the risk management practices and firm performance. Practitioners should be aware that the control mechanisms have different moderating effects, i.e. different type of control mechanism should be employed to facilitate the risk management practices in order to achieve a better firm performance.